SynAggreg: A Multifunctional High-Throughput Technology for Precision Study of Amyloid Aggregation and Systematic Discovery of Synergistic Inhibitor Compounds. Issue 24 (7th December 2018) - Aviolat, Hubert; Nominé, Yves; Gioria, Sophie; Bonhoure, Anna; Hoffmann, David; Ruhlmann, Christine; Nierengarten, Hélène; Ruffenach, Frank; Villa, Pascal; Trottier, Yvon; Klein, Fabrice A.C.
Abstract: Numerous proteins can coalesce into amyloid self-assemblies, which are responsible for a class of diseases called amyloidoses, but which can also fulfill important biological functions and are of great interest for biotechnology. Amyloid aggregation is a complex multi-step process, poorly prone to detailed structural studies. Therefore, small molecules interacting with amyloids are often used as tools to probe the amyloid aggregation pathway and in some cases to treat amyloidoses as they prevent pathogenic protein aggregation. Here, we report on SynAggreg, an in vitro high-throughput (HT) platform dedicated to the precision study of amyloid aggregation and the effect of modulator compounds. SynAggreg relies on an accurate bi-fluorescent amyloid-tracer readout that overcomes some limitations of existing HT methods. It allows addressing diverse aspects of aggregation modulation that are critical for pathomechanistic studies, such as the specificity of compounds toward various amyloids and their effects on aggregation kinetics, as well as the co-assembly propensity of distinct amyloids and the influence of prion-like seeding on self-assembly. Furthermore, SynAggreg is the first HT technology that integrates tailored methodology to systematically identify synergistic compound combinations—an emerging strategy to improve fatal amyloidoses by targeting multiple steps of the aggregation pathway. To this end, we apply analytical combinatorial scores to rank the inhibition efficiency of couples of compounds and to readily detect synergism. Finally, the SynAggreg platform should be suited for the characterization of a broad class of amyloids, whether of interest for drug development purposes, for fundamental research on amyloid functions, or for biotechnological applications. Graphical Abstract: Highlights: Advanced HT technology to study amyloid aggregation and modulator compounds Bi-fluorescent tracer readout overcoming the limitations of existing HT methods Screening for synergistic compound combinations of therapeutic interest Integration of automated data analysis and mathematical models to identify synergy Multifunctional toolbox for fundamental and applied research in the amyloid field